Case Study 4: Digital Storytelling. (1st September 2018) - Burns, Tom; Sinfield, Sandra; Abegglen, Sandra
This is Case Study 4 of 5, as introduced in 'Regenring academic writing' on pp. 181–90, which includes an overview of the context for all five pieces.